Seasonal changes in crop growth and grain yield of different japonica rice cultivars in southeast China. (9th January 2020) - Chen, Song; Liu, Shaowen; Yin, Min; Zheng, Xi; Chu, Guang; Xu, Chunmei; Wang, Dangying; Zhang, Xiufu
Abstract: It is unknown whether japonica rice bred up in the single season is suitable for growing in the late season in southeastern China. To evaluate the response of grain yield and growth traits of japonica varieties to the changing growing season, two types of japonica rice (inbred japonica and indica‐japonica hybrid rice) were planted during single and late seasons in 2016 and 2017. The grain yields of indica‐japonica hybrid rice were 8.3–9.5 t ha −1 and 9.2–10.8 t ha −1 in the late and single season, respectively, which were significantly greater than those of japonica inbred rice. In addition, the grain yields decreased when the growing season was switched from the single to the late season, being 17.3–23.7% for the inbred japonica rice and 4.0–9.7% for the indica‐japonica hybrid rice, indicating a small yield gap between the single and late season of the indica‐japonica hybrid rice. Furthermore, the indica‐japonica hybrid rice had a higher accumulated biomass, leaf area index (LAI), and spikelets per panicle; comparable phenological traits and leaf photosynthetic rate during panicle development; but lower grain weight and grain filling percentage compared with those of the inbred japonica rice. These results suggested that high grain yield of the indica‐japonica hybrid rice during the late season might be attributed to the high accumulation of biomass and the large panicle size. Thereby, we suggested that the great LAI during panicle development, high biomass accumulation before heading, and large panicle size might be useful as indicators for breeding the japonica variety during the late season.